An integrated approach to electricity sector reforms in the resource rich economies of the MENA. (March 2020) - Poudineh, Rahmatallah; Sen, Anupama; Fattouh, Bassam
Abstract: This paper argues that MENA resource-rich economies must go beyond simply replicating the "standard model" of electricity market liberalisation. They need to not only adapt the standard model to their unique contexts but also integrate it with other elements of their energy systems through harnessing complementarities between existing policies. The integrated model therefore includes additional modules: rationalising end user prices, improving energy efficiency, integrating renewables, and collapsing the "silos" between different energy vectors. The success of the extended reform model, however, is crucially contingent upon taking into account three particular factors in its implementation. First, reforming energy prices requires a better understanding of the underpinning logic of subsidies beyond popular justifications around the "social contract" or "political compact". Second, energy efficiency is a challenging initiative in the MENA region, which the correction of price signals can only partially resolve, due to other factors that influence it, such as path dependency, market failures and consumer behaviour. And third, incentivising investments in renewable energy requires careful design of the balance of roles between the market and government, as renewable support schemes may lead to an increased role for centralised coordination, thereby contradicting the originally intended objectives of electricity market reform. Highlights: MENA electricity reform must go beyond replicating the "standard model". We propose an integrated approach to electricity sector reforms in the region. It extends the standard model to harness synergies between existing policies. However, this extension means special attention needs to be paid to implementation.